Discontinous change from thermally- to geometrically-dominated effective interactions in colloidal solutions. Issue 48 (21st November 2016) - Gnan, Nicoletta; Sciortino, Francesco; Zaccarelli, Emanuela
Abstract : In a colloidal suspension, effective interactions induced by a self-assembling cosolute are controlled by thermal fluctuations as long as the bond lifetime is finite. Only for infinite bond lifetime the effective interactions depend on the geometric properties of the cosolute. Abstract : We report numerical results for the effective potential arising between two colloids immersed in a self-assembling cosolute which forms reversible clusters. The potential is evaluated at cosolute state points with different densities and temperatures but with the same connectivity properties. We find that the range of the resulting effective potential is controlled only by the cosolute thermal correlation length rather than by its connectivity length. We discuss the significant differences from previous results focusing on the cosolute forming irreversible clusters and we show that the irreversible bond case represents a singular limit which cannot be accessed in equilibrium by continuously increasing the bond lifetime.